Economic Impact of Practicing IPM Technology on Bitter Gourd (Momordica charantia L.) Production in Comilla District of Bangladesh - Islam, S; Islam, D M S; Khanum, R (The Agriculturists, 2018)
The present study was conducted to assess the economic impact of practicing Integrated Pest Management technology on bitter gourd production in Chandina upazila under Comilla district of Bangladesh. Sample survey was carried out over 70 bitter gourd producing farms. Out of 70 farmers, 35 for IPM and 35 for Non-IPM farmers were selected. The study revealed that majority of the farmers had moderately favorable attitude towards IPM technology for producing bitter gourd as shown by farmers’ attitude index. IPM farmers earned more profit than Non-IPM farmers on bitter gourd production. The average total cost of bitter gourd production per hectare was estimated at about Tk 3,68,335 and 4,44,508 for IPM and Non-IPM farmers, respectively. The average gross returns per hectare were found at about Tk 8,60,016; 8,55,642; and 8,15,947 for marginal, small and medium IPM farmers, respectively. The same were Tk 8,22,654; 7,53,373 and 7,48,255 for marginal, small, and medium Non-IPM farmers, respectively. The estimated BCR was higher for IPM farmers (2.29) than Non-IPM farmers (1.69). Partial budget analysis showed that IPM technology was more profitable and net benefit was Tk 1,61,557. Although bitter gourd production was profitable, farmers faced several problems such as lack of training and technical knowledge, inadequate extension services, lack of marketing facilities etc. in using IPM technology. The Agriculturists 2017; 15(2) 11-23